Compact multilayer self‐packaged filter with surface‐mounted packaging. Issue 7 (1st April 2015) - Ma, K.; Fan, L.; Zhang, S.
Abstract : A new self‐packaged bandpass filter by using multilayer print circuit board technology is proposed and investigated. By using a multilayer structure, a lumped step‐impedance resonator as well as self‐packaging, the designed filter can achieve a much more compact size, low insertion loss and a wide stopband. The implemented filter operated at a centre frequency of 800 MHz with a 3 dB bandwidth of 120 MHz demonstrates stopband rejection better than 25 dB up to 4 GHz. The measured insertion loss including the connector loss in the input and output is 1.48 dB. The size of the filter is only 12 × 8 mm, i.e. 0.059 λ g × 0.039 λ g .